Culture and mathematics learning: Identifying students’ mathematics connection - Al Kusaeri; Habib Husnial Pardi; Abdul Quddus (Universitas Islam Negeri (UIN) Mataram, 2019)
[English]: Mathematics connection support students finding various possible strategies in problem-solving. Cultural products can be used as mathematical objects in learning. This article, part of a study that designed culture-based learning, aims to identify students' mathematics connection. Data was collected through a test given to 341 students and unstructured interviews of nine students selected based on the completion of the test, which fulfills mathematization steps. Data analysis began by classifying students’ answers based on mathematization, identifying mathematics connection of students according to mathematization, analyzing students’ mathematics connection, and drawing conclusions about mathematics connection and the constraints found. The results showed that students' mathematics connections include three categories, namely understanding connection, representation connection, and justification connection. Students with justification connection solved mathematical problems according to mathematization steps, from the identification of mathematical objects to formal mathematics. Meanwhile, students with understanding and representation connection solved their respective mathematical problems up to the concrete and formal stages. The findings reveal that culture-based mathematics learning provides space to understand students' mathematics connection. Further research is required to prove that it can be used to develop students' mathematics connection. Keywords: Mathematics learning, Culture, Mathematics connection [Bahasa]: Koneksi matematika mendukung siswa menemukan berbagai kemungkinan strategi dalam penyelesaian masalah. Produk budaya memungkinkan dapat dijadikan objek matematika dalam pembelajaran. Artikel ini merupakan bagian dari penelitian yang merancang desain pembelajaran berbasis budaya lokal yang bertujuan mengidentifikasi kemampuan koneksi matematika siswa. Data dikumpulkan melalui tes yang diberikan kepada 341 siswa dan wawancara tidak terstruktur terhadap 9 siswa yang dipilih berdasarkan penyelesaian tes sesuai proses matematisasi. Analisis data diawali dengan klasifikasi jawaban siswa berdasarkan tahapan matematisasi, identifikasi kemampuan koneksi matematika sesuai tahapan matematisasi, analisis kemampuan koneksi matematis, dan penarikan simpulan terkait kemampuan koneksi matematika serta kendala yang ditemukan. Hasil penelitian menunjukkan bahwa kemampuan koneksi matematika siswa meliputi tiga kategori yaitu koneksi pemahaman, koneksi representasi, dan koneksi justifikasi. Siswa dengan kemampuan koneksi justifikasi bisa menyelesaikan masalah matematika sesuai tahapan matematisasi, dari identifikasi objek matematika sampai matematika formal. Sementara itu, siswa yang memiliki kemampuan koneksi pemahaman dan representasi menyelesaikan masalah matematika masing-masing sampai pada tahap model kongkret dan model formal. Hasil penelitian menunjukkan bahwa pembelajaran berbasis budaya memberikan ruang untuk memahami kemampuan koneksi matematika siswa. Penelitian lebih lanjut dibutuhkan untuk menunjukkan pembelajaran berbasis budaya bisa digunakan untuk mengembangkan kemampuan koneksi matematika siswa. Kata Kunci: Pembelajaran matematika, Budaya, Koneksi matematika